2020
DOI: 10.1111/jvh.13351
|View full text |Cite
|
Sign up to set email alerts
|

Virology analysis of chronic hepatitis B virus–infected patients treated for 28 days with JNJ‐56136379 monotherapy

Abstract: Four weeks of once-daily oral JNJ-56136379 (JNJ-6379; 25, 75, 150 or 250 mg), a class-N capsid assembly modulator (CAM-N), was well tolerated with potent antiviral activity in treatment-naïve, chronic hepatitis B e antigen-positive and hepatitis B e antigen-negative patients (NCT02662712). Hepatitis B virus (HBV) genome sequence analysis, using HBV DNA next-generation sequence technology, was performed, and impact of substitutions on efficacy was assessed. Analyses focused on HBV core protein amino acid positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Pre‐existing and emergent core protein variants associated with reduced susceptibility have been noted in other CI clinical programs, including T109M [ 13 ] and F23Y, T33N, I105T, and Y118F. [ 20 , 21 , 22 ]…”
Section: Resultsmentioning
confidence: 99%
“…Pre‐existing and emergent core protein variants associated with reduced susceptibility have been noted in other CI clinical programs, including T109M [ 13 ] and F23Y, T33N, I105T, and Y118F. [ 20 , 21 , 22 ]…”
Section: Resultsmentioning
confidence: 99%
“…A review of the available HBV sequence databases ( https://hbvdb.lyon.inserm.fr/HBVdb/ ) indicates that except for the Y38F variant (3.2%), none of the substitutions studied preexist as a natural polymorph in >1% of patient isolates ( Table 5 ). Currently, multiple classes of CIs are still in early-stage clinical development (phases 1 and 2) ( 23 , 24 ), and clinical baseline polymorphisms and on-treatment enrichment of substitutions reducing the in vitro activity of CIs are rare, with a few impacting the virological response ( 23 , 24 ). In the phase 1b study ABI-H0731-101(B), there was one HBeAg-negative patient who exhibited only a 1.0-log decline by day 28 on monotherapy, who was subsequently found to harbor a known CI-resistant variant (T109M) at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, JNJ 6379 proceeded into 48 week phase 2 trials initially comprising monotherapy and several combination arms (JADE study NCT03361956). Different from the four-week treatment in phase 1 [ 247 ] drug-associated viral breakthrough was seen in some patients after 24 weeks of monotherapy but not in combination with a NUC [ 248 ]; the combination also achieved higher HBV suppression than NUC alone [ 229 ], especially in treatment-naïve HBeAg + CHB patients. Moreover, a higher fraction of these patients showed more pronounced (though still modest) reductions in HBsAg and HBeAg levels, often associated with flares of elevated serum alanine transaminase (ALT) levels, in line with liver inflammation.…”
Section: Targeting Hbv Capsid Dynamicsmentioning
confidence: 99%
“…Notably, natural polymorphisms have been found at HAP pocket positions by searches in HBV databases [ 261 ] and a large patient cohort [ 260 ], including Y118F and D29A, I105T/L/V and T114I/V but not T33N; the presence or absence of such baseline mutations may thus affect treatment outcome in patients, as seen by 20-fold reduced activity to AB-506 to Cp baseline mutant I105T [ 262 ]. In an early 28-day trial with JNJ-6379 half of the patients carried viruses with one or more potentially relevant mutations, including Y118F, I105T, T109M, and T019I, but their therapy response was not generally reduced, despite a detectable enrichment of the Y118F mutant [ 247 ]. Importantly, though, 24 week interim data from the JNJ-6379 monotherapy arm of the 48 week JADE study revealed viral breakthrough in several patients which correlated with baseline mutations Y118F and I105T and emergence of the T33N mutation [ 248 ].…”
Section: Targeting Hbv Capsid Dynamicsmentioning
confidence: 99%